2002
DOI: 10.3141/1803-05
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Behavioral Adaptation to Lane Departure Warnings

Abstract: Behavioral adaptation describes the collection of behaviors that occur after a change in the road traffic system. Typically, those behaviors not intended by the initiators of the change having a negative impact on safety are of particular interest. Although behavioral adaptation is frequently cited as an explanatory variable for observed discrepancies between engineering estimates and actual outcomes of safety interventions, a thorough understanding of behavioral adaptation does not, at present, exist. Most th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(47 citation statements)
references
References 13 publications
5
41
1
Order By: Relevance
“…These results are in line with measurements of speed and lateral position in traffic flow made in a pre-study [34] showing a speed reduction of 2 km/h in average and a change in lateral position of 5 cm to the right (right hand traffic). In relation to in-vehicle LDW systems an evaluation whether a LDW system would induce BA was done [35]. Results showed that drivers with LDW systems tend to overreliance on such systems which might lead to less positive safety effect.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in line with measurements of speed and lateral position in traffic flow made in a pre-study [34] showing a speed reduction of 2 km/h in average and a change in lateral position of 5 cm to the right (right hand traffic). In relation to in-vehicle LDW systems an evaluation whether a LDW system would induce BA was done [35]. Results showed that drivers with LDW systems tend to overreliance on such systems which might lead to less positive safety effect.…”
Section: Discussionmentioning
confidence: 99%
“…Someone who believes he/she can control events has an internal locus of control, whereas those who do not believe it are external. Concerning partially automated driving and locus of control, overconfidence is more salient for drivers with an external locus of control than those with an internal locus of control; this result has been observed on a simulator but not on a test-track (Rudin-Brown & Noy, 2002). Yet, locus of control was not affected by simulated partial automation (i.e.…”
Section: Behavioral Adaptation Personality Traits and New Driving Tementioning
confidence: 91%
“…Among studies on behavioral adaptation to ADAS, one of the main findings is that locus of control and sensation seeking are personality traits which could have an influence on driving behavior when using ADAS (Rudin-Brown & Noy, 2002;Rudin-Brown & Parker, 2004;Stanton & Marsden, 1996;Ward, Fairclough, & Humphreys, 1995).…”
Section: Behavioral Adaptation Personality Traits and New Driving Tementioning
confidence: 99%
See 1 more Smart Citation
“…Second, the secondary task was designed to foster drivers' reliance on the lane keeping assistance systems by generating a resource-demanding dual-task situation (cp. Rudin-Brown & Noy, 2002). The aim was to manipulate task demands in a way that encourages drivers to rely on the lane keeping assistance systems as a strategy to limit the expenditure of mental effort in the driving task while maintaining or even improving concurrent task performance.…”
Section: Measurement Of Drivers' Reliance On the Lane Keeping Assistamentioning
confidence: 99%